2003
DOI: 10.1007/bf02344887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of applanation resonator sensors for intra-ocular pressure measurement: Results from clinical andin vitro studies

Abstract: Glaucoma is an eye disease that, in its most common form, is characterised by high intra-ocular pressure (IOP), reduced visual field and optic nerve damage. For diagnostic purposes and for follow-up after treatment, it is important to have simple and reliable methods for measuring IOP. Recently, an applanation resonator sensor (ARS) for measuring IOP was introduced and evaluated using an in vitro pig-eye model. In the present study, the first clinical evaluation of the same probe has been carried out, with exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 10 publications
(14 reference statements)
0
28
0
Order By: Relevance
“…The resonance sensor has also been studied [3] for the measurement of intraocular pressure (IOP) of the eye to detect glaucoma. Measurements on pig eyes in vitro correlated well with the IOP [5]. Further development of the sensor system showed that a spherical contact surface was preferred because that made the sensor less dependent on variations in surface topography.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The resonance sensor has also been studied [3] for the measurement of intraocular pressure (IOP) of the eye to detect glaucoma. Measurements on pig eyes in vitro correlated well with the IOP [5]. Further development of the sensor system showed that a spherical contact surface was preferred because that made the sensor less dependent on variations in surface topography.…”
mentioning
confidence: 63%
“…A hemi-spherical tip will not subject the object to as large forces as a flat one of same diameter, at a certain impression depth. Also, Eklund et al [5] concluded that a spherical tip is preferred instead of a flat tip because off-center loads of the sensor tip would be avoided. These off-center loads could be received due to an irregular or inclined surface when measuring on prostate tissue.…”
Section: Comparison Of Silicone and Prostate Tissue In Vitromentioning
confidence: 98%
“…This frequency shift is proportional to the contact area. 21 A force transducer measures the force needed to applanate the cornea. Both contact area and force are sampled continuously with a 1 kHz sampling rate.…”
Section: Tonometry Methodsmentioning
confidence: 99%
“…There were six repeated measurements on five different positions, centre position and four 1.0 mm off-centre positions (at 3, 6, 9, and 12 o'clock on the cornea) [5,6].…”
Section: Bench Test Measurementsmentioning
confidence: 99%